Material Deterioration Detection of Wooden Columns at the Nanyang Fuya Museum Using a Combination of Macroscopic Visual Inspection and Moisture Content Testing - Yan Yang; Chunge Song; Limei Liang; Minghui Tao; Fuqun Wang; Ying Zhao (BioResources, 2023)
Wooden columns, as an important load-bearing wooden component of traditional wooden structures, determine the safety of an entire building. With the increase in material deterioration, the overall health and life of ancient buildings is affected. In this study, the deterioration of wooden columns of ancient buildings in the central axis of the Nanyang Fuya Museum was detected through a combination of macroscopic visual inspection and moisture content testing. The result was that the deterioration degrees and MCs of wooden columns located in the south direction, with good ventilation effect or with oil paint protection were lower than those of wooden columns located in the north direction, with poor ventilation effect or without oil paint protection. The deterioration degree increased with the increase of MC. The results of this research provide the basis for the analysis of the causes and risks of material deterioration.